Multilevel Inverse-Based Factorization Preconditioner for Solving Sparse Linear Systems in Electromagnetics - Yiming Bu; Bruno Carpentieri; Zhaoli Shen; Tingzhu Huang (Applied Computational Electromagnetics Society Journal (ACES), 2021)
We introduce an algebraic recursive multilevel approximate inverse-based preconditioner, based on a distributed Schur complement formulation. The proposed preconditioner combines recursive combinatorial algorithms and multilevel mechanisms to maximize sparsity during the factorization.